The Global Burden of Clostridioides difficile Infections, 2016–2024: A Systematic Review and Meta-Analysis - Rachel A. A. Akorful; Alex Odoom; Aaron Awere-Duodu; Eric S. Donkor (Infectious Disease Reports)
Background: Clostridioides difficile infection (CDI) is a major cause of healthcare-associated infections globally. Understanding variations in CDI incidence and outcomes across settings, populations, and regions is important for guiding prevention strategies. Aim: The aim of this study was to determine the global epidemiology of CDI to better understand disease burden across settings and geographic regions. Methods: Relevant publications were identified through searches of major databases, including PubMed, Scopus, and Web of Science, published from 1 January 2016 through 24 July 2024. Random effects models were used to pool estimates, and 95% confidence intervals (CIs) were calculated. Results: A total of 59 studies, representing 24 countries across North America, Europe, the Asia–Pacific region, Latin America, and the Middle East, met the inclusion criteria. The incidence of CDI was highest in hospital-onset healthcare facility settings, with 5.31 cases/1000 admissions (95% CI 3.76–7.12) and 5.00 cases/10,000 patient-days (95% CI 3.96–6.15). Long-term care facilities reported 44.24 cases/10,000 patient-days (95% CI 39.57–49.17). Pediatric populations faced a greater risk, with 4.52 cases/1000 admissions (95% CI 0.55–12.17), than adults did at 2.13 (95% CI 1.69–2.61). Recurrence rates were highest for community-acquired CDI at 16.22%. The death rates for the CDI cases tracked for 30 days and of unspecified duration were 8.32% and 16.05%, respectively. Conclusions: This comprehensive review identified healthcare facilities, long-term care, pediatric populations, and North America as disproportionately burdened. This finding provides guidance on priority areas and populations for targeted prevention through antimicrobial stewardship, infection control, and surveillance.